Non-medical Use of Prescription Stimulants Among College Students: Non-oral Routes of Administration, Risk Factors, Motivations, and Pathways - Butler, Stephen F.; Faraone, Stephen V.; Rostain, Anthony L.; Newcorn, Jeffrey H.; Antshel, Kevin M.; Robbins, Rebekkah S.; Green, Jody L. (Frontiers in Psychiatry, 2021)
Introduction: Nonmedical use (NMU) of prescription stimulant medications is a continuing public health concern. Stimulant medications prescribed for attention-deficit/hyperactivity disorder (ADHD) are widely available on college campuses, and college students may have multiple opportunities to engage in prescription stimulant NMU. This online self-report survey examined prescription stimulant NMU among college students, including: (1) patterns of non-oral route of administration (ROA); (2) motivations for non-oral ROAs; and (3) retrospectively recalled pathways of initiation. Method: The survey sample was created from a pool of 3,379 respondents matched to a sampling frame constructed from the 18-26-year-old, college student sample of the 2016 American Community Survey (ACS). About 14% of the pool were college students with self-reported prescription stimulant NMU. The survey covered user characteristics, prescription and illicit substance use, age of first NMU, motivations for NMU, sources of procurement, and ROAs used. Results: Among 486 students reporting prescription stimulant NMU, 43% had a lifetime diagnosis of ADHD. More than 90% reported polysubstance use, with 55% using illicit substances other than marijuana. Slightly more than 2 in 5 (43.3%) reported using illicit substances prior to prescription stimulant NMU, 24.6% used both at the same age, and 32.0% engaged in NMU of prescription stimulants prior to using illicit substances. Prescription stimulant NMU preceded prescription opioid NMU 45% of the time. More than a quarter of those engaged in prescription stimulant NMU (27.9%) initiated prescription stimulants alone or at the same age as other drugs. Most prescription stimulant NMU was oral, however 23.0% reported any nonoral use: snorting (20.4%), smoking (6.0%) or injection (3.5%). Nonoral use was associated with being male, obtaining medication from a dealer, use to get high, and/or a substance use disorder diagnosis. Conclusions: Prescription stimulant NMU often occurs in the context of polysubstance use among college students. Injection, an under-researched route for prescription stimulants, was associated with male gender, history of substance use and higher likelihood of illicit substance use. Nearly a quarter of college student survey respondents reported use with non-oral routes, which is associated with other high-risk behaviors. Efforts to reduce non-oral prescription stimulant NMU in college students are warranted.